Filterisasi Budaya K-Pop pada Remaja: Studi Kasus pada Siswa SMK Negeri 2 Pekanbaru - Qori Islami Aris; Essy Syam; Mohd Fauzi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service activity is entitled "Filtering K-Pop Culture in Teenagers: Case Study on Students of SMK Negeri 2 Pekanbaru". This community service activity seeks to introduce foreign cultures that enter Indonesia and make significant changes starting from the mindset, behavior, and even the lifestyle of teenagers. KPop culture or known as Hallyu has successfully influenced people's lives, especially teenagers. Teenagers have a high tendency to imitate the lifestyle and attitudes presented by K-Pop culture, such as imitating the style and fashion of idols and even often using Korean when meeting with their friends who both love K-Pop. This is the background for the service team to introduce the ideology carried by K-Pop culture and the negative impacts it causes.